Penile Prosthesis Implantation for Treatment of Postpriapism Erectile Dysfunction - Durazi, Mohammed H; Jalal, Akbar A (Urology Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Our aim was to evaluate the procedure and outcome of penile prosthesis surgery in the treatment of men with postpriapism erectile dysfunction. Materials and Methods: During the period between 1997 and 2004, a total of 17 patients with postpriapism erectile dysfunction underwent penile prosthesis implantation at our institution. Prosthesis implantation was done electively 6 to 18 months after priapism, when the patients presented with erectile dysfunction. Of the prosthesis implanted, 11 were malleable, 4 were 2-piece, and 2 were 3-piece prostheses (AMS, Minnetonka, Minnesota, USA).Â Â Â Â Results: All the 17 patients were successfully implanted with penile prosthesis. Intra-operatively, corporeal dilation was difficult due to extensive corporeal fibrosis, which led to urethral injury in 2 patients. There were no major postoperative complications. The median hospital stay was 5 days. The follow-up period ranged from 2 to 9 years (median, 6 years). All the patients were satisfied with the prosthesis. Conclusion: Penile prosthesis implantation is the modality of treatment for patients with postpriapism erectile dysfunction at our institution. It has a high patient satisfaction rate. Although procedure-related complications are common due to corporeal fibrosis, they were mostly minor ones and did not affect the outcome of the procedure.